Aberrant miR-3135b and miR-1273g-3p expression in the peripheral blood samples of BRCA1/2 (±) ovarian cancer patients - Seref Bugra Tuncer; Betul Celik; Seda Kılıc Erciyas; Ozge Sukruoglu Erdogan; Ozge Pasin; Mukaddes Avsar; Busra Kurt Gultaslar; Arash Adamnejad Ghafour; Gamze Uyaroglu; Demet Akdeniz Odemis; Hulya Yazıcı (Heliyon, 2024)
Ovarian cancer (OC) ranks as the eighth most prevalent malignancy among women globally. The short non-coding RNA molecules, microRNAs (miRNAs) target multiple mRNAs and regulate the gene expression. Here in this study, we aimed to validate miR-3135b and miR-1273g-3p as novel biomarkers for prognostic and diagnostic factor OC. After RNA isolation, we analyzed the miR-3135b and miR-1273g-3p expression in peripheral blood samples derived from 150 OC patients. Subsequently, we compared their expression levels with 100 healthy controls. The differences of miR-3135b and miR-1273g-3p expression were detected using the Quantitative Real Time-PCR (qRT-PCR) technique following miRNA-specific cDNA synthesis pursing miRNA separation. The miR-3135b and miR-1273g-3p were higher in OC patients who tested positive for BRCA1/2 compared to BRCA-negative patients, and healthy cases. The level of miR-3135b demonstrated a roughly 4.82-fold increase in OC patients in comparison to the healthy cases, while miR-1273g-3p expression exhibited a roughly 6.77-fold increase. The receiver operating characteristic (ROC) analysis has demonstrated the potential of miR-3135b and miR-1273g-3p as markers for distinguishing between OC patients and healthy controls. The higher expressions of miR-3135b and miR-1273g-3p could be associated with OC development. Moreover, miR-3135b may have a diagnostic potential and miR-1273g-3p may have both diagnostic and prognostic potential in OC cell differentiation. The string analysis has revealed an association between miR-1273g-3p and the MDM2 gene, suggesting a potential link to tumor formation through the proteasomal degradation of the TP53 tumor suppressor gene. Additionally, the analysis indicates an association of miR-1273g-3p with CHEK1, a gene involved in checkpoint-mediated cell cycle arrest. String analysis also indicates that miR-3135b is associated with the MAPK1 gene, causing activation of the oncogenesis cascade. In conclusion, miR-1273g-3p, and miR-3135b exhibit significant potential as diagnostic markers. However, further research is needed to comprehensively investigate these miRNAs diagnostic and predictive characteristics in a larger cohort.